Recovery in elite youth basketball players: The responsiveness of the psychophysiological measurements and the role of testosterone concentration - Marino, T. K.; Morgans, R.; Schultz de Arruda, A. F.; Aoki, M. S.; Drago, G.; Moscaleski, L. A.; Morya, E.; Okano, A. H.; Moreira, A. (Journal of Sports Sciences, 2024)
This study investigated the recovery responses to the Total Quality Recovery (TQR), Well-Being questionnaire (WBQ), and Heart Rate (HR) responses to Submaximal Running Test (SRT), and the influence of salivary testosterone concentration (TEST) on these responses in 25 elite youth (U15) male basketball players. TQR, WBQ, and HR measurements were assessed after 48 hours of rest (T1), 24 hours after the 1st day of training (T2) and 24 hours after the 2nd day of training (T3). Salivary sampling was conducted at T1 and T3. A significant decrease was observed for TQR (F = 4.06; p = 0.01) and for WBQ (F = 5.37; p = 0.008) from T1 to T3. No difference among the three-time points was observed for HR and HR Recovery, and the TEST concentration did not influence the results. These results show that TQR and WBQ are sensitive to acute transient alterations in training loads (TL) and may be utilized to monitor recovery in elite youth basketball players. The HR related measurements presented limited responsiveness, and the TEST seems not to influence the recovery of these players who are competing at highest performance level.